Uji Reliabilitas Sendai Framework for Disaster Risk Reduction Dalam Rehabilitasi Kawasan Ekonomi Khusus Tanjung Lesung - Karina Stefanie; Natalia Yeti Puspita (Jurnal Hukum IUS QUIA IUSTUM, 2021)
State has the main responsibility in any disaster management process. The Sendai Framework for Disaster Risk Reduction (SFDR) is an international disaster management agreement in a country which Indonesia also ratifies. The research objective is to determine how the reliability test of the SFDRR in the rehabilitation of the Tanjung Lesung Special Economic Zone (KEK) after the 2018 tsunami. This research is an empirical juridical study, primary data as the main data obtained from field research and interviews, as a complement, a literature study was conducted to obtain secondary data. The results of the study concluded that rehabilitation efforts based on the SFDRR had been carried out by the government but there were no direct coordination and communication between the government, KEK managers, local communities, and tourists.